Leaning-Based 360° Interfaces: Investigating Virtual Reality Navigation Interfaces with Leaning-Based-Translation and Full-Rotation - Hashemian, Abraham M.; Riecke, Bernhard E. (Virtual, Augmented and Mixed Reality (VAMR 2017), 2017)
Despite recent advances in high quality Head-Mounted Displays (HMDs), designing locomotion interfaces for Virtual Reality (VR) is still challenging, and might contribute to unwanted side effects such as disorientation and motion sickness. To address these issues, we investigated the potentials of leaning-based 360° locomotion interfaces, which provide full-rotational motion cues (unlimited 360° rotations) for rotation, and leaning-based translational motion cues for forward/backward and sideways translation. In this experiment we compared joystick with three locomotion interfaces: Real-Rotation (rotation control by an office swivel chair and forward/backward and sideways translations by joystick); Swivel-Chair (rotation control by the swivel chair and forward/backward and sideways control by leaning forward/backward and sideways on the chair respectively); NaviChair (rotation control by a sit/stand stool and forward/backward and sideway control by weight shifting and leaning in the same direction, which is sensed by a Nintendo’s Wii balance board pressure sensors the stool is mounted on). We asked participants to follow an avatar in an unpredictable curvilinear path in a gamified experiment to evaluate interfaces in terms of different usability aspects, including accuracy, motion sickness, sensation of self-motion, presence, immersion, ease of use, ease of learning, engagement, enjoyment, overall preference, etc. Results did not show any significant advantages of our suggested interfaces over the joystick. But in a sense this is promising because in many aspects, the usability of the proposed interfaces was similar to the well-trained joystick. Moreover, our interfaces had slightly lower motion sickness ratings, and higher sensation of self-motion and spatial presence ratings than the joystick. However, they showed controllability issues, which resulted in significantly lower navigation accuracy (i.e., distance errors) and reduced control precision ratings, which made them less easy to use and comfortable than joystick. We also discuss the participants’ qualitative feedbacks about our interfaces, which shows their strengths and weaknesses, and guide the design of more embodied future VR locomotion interfaces.
Keywords: Riecke; Riecke_2017; abraham-hashemian; bernhard-riecke; book-chapter; conferencePaper; iat802; iat802_fall2016; leaning-based interfaces; motion-cueing; proj--motionCueingInterfaces